2000
DOI: 10.1002/(sici)1521-3765(20000103)6:1<139::aid-chem139>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Mechanisms of Enantioselective Hydrogenation of Simple Olefins with Chiral Rhodium Catalysts in the Presence of Anions

Abstract: The strong influence of various anions upon the hydrogenation of 2-phenyl-1-butene, catalyzed by chiral rhodium catalysts was investigated. Both sulfonates and halides exert large increases in the enantioselectivity when [Rh[(-)-bdpp](NBD)]ClO4 (bdpp = 2,4-bis(diphenylphosphino)pentane, NBD = 2,5-norbornadiene) is used as the catalyst precursor at high pressures (70 atm) of dihydrogen in nonpolar solvents. A dihydride mechanism similar to that for Wilkinson's catalyst [RhCl(PPh3)3] was shown to be operating at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…The mechanisms of the ortho/para conversion of hydrogen have been the topic of various experimental and theoretical studies. This interest in the conversion was triggered by three main reasons, namely (i) the application of combined studies of the ortho/para spin conversion of dihydrogen and of the hydrogen/deuterium scrambling reactions as tools for the elucidation of the mechanisms of catalytic hydrogenation reactions; 3,4 (ii) the application of para-hydrogen as an agent for the sensitivity enhancement of liquid state NMR, [5][6][7] in particular for studies of catalysis; and (iii) the quantum mechanical nature of the ortho-and para-states, which is interesting by itself; (iv) the usage of ortho/para-water ratios as remote sensors for the thermal history of the ice core of comets; 8-11 (v) to understand the mechanisms of the conversion of para-formaldehyde to ortho-formaldehyde by surface adsorption. 12 The studies of dihydrogen metal complexes started when Wilkinson found the first catalysts which are able to take up and easily activate molecular dihydrogen during the hydrogenation of double bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of the ortho/para conversion of hydrogen have been the topic of various experimental and theoretical studies. This interest in the conversion was triggered by three main reasons, namely (i) the application of combined studies of the ortho/para spin conversion of dihydrogen and of the hydrogen/deuterium scrambling reactions as tools for the elucidation of the mechanisms of catalytic hydrogenation reactions; 3,4 (ii) the application of para-hydrogen as an agent for the sensitivity enhancement of liquid state NMR, [5][6][7] in particular for studies of catalysis; and (iii) the quantum mechanical nature of the ortho-and para-states, which is interesting by itself; (iv) the usage of ortho/para-water ratios as remote sensors for the thermal history of the ice core of comets; 8-11 (v) to understand the mechanisms of the conversion of para-formaldehyde to ortho-formaldehyde by surface adsorption. 12 The studies of dihydrogen metal complexes started when Wilkinson found the first catalysts which are able to take up and easily activate molecular dihydrogen during the hydrogenation of double bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of solvents with different polarity rules out a reliable comparison between the tethered and homogeneous catalysts, one may draw out some general conclusions: i) The hydrogen-bonding immobilization of the [(R)-(R)-BDPBzPSO 3 ] À and BINAP complexes on silica does not reduce the enantioselectivity (this latter is intrinsically low for the catalyst/substrate systems employed in this work). [12,13,14] ii) The supported DIOP complex is less enantioselective than the homogeneous derivative, which may tentatively be related to the presence of ether oxygen atoms in the ligand backbone and hence to possible H-bonding interactions with the support leading to less efficient enantio-discrimination. However, a different hydrogenation mechanism in the two-phase systems cannot be ruled out.…”
Section: Methodsmentioning
confidence: 99%
“…553 He also worked on the enantioselective hydrogenation of double bonds (e.g. of olefins with chiral rhodium catalysts, 554 of imines with iridium catalysts 555 ), on the isomerization of allyl alcohols, 556 as well as on other subjects related to organometallic catalysis.…”
Section: Strasbourg Chemistry After the 2nd World Warmentioning
confidence: 99%